The Publicity “Defect” of Customary Law - Gauri, Varun (2012)
This paper examines the extent to which dispute resolvers in customary law systems provide widely understandable justifications for their decisions. The paper first examines the liberal-democratic reasons for the importance of publicity, understood to be wide accessibility of legal justification, by reviewing the uses of publicity in Habermas and Rawls accounts of the rule of law. Taking examples from Sierra Leone, the paper then argues that customary law systems would benefit from making the reasons for local dispute resolution practices, such as "begging" from elders, witchcraft, and openness of hearings, more widely accessible. The paper concludes that although legal pluralism is usually taken to be an analytical concept, it may have a normative thrust as well, and that publicity standards would also apply to formal courts in developing countries, which are also typically "defective" along this dimension.